Analisis Green economy Sebagai Paradigma Bank Syariah Indonesia Dalam Mendukung Sustainability Green Banking - Purnama, Ira; Anggraini, Tuti (Fakultas Ekonomi Universitas Gresik, 2023)
Many countries are currently facing the problem of depletion or decline of energy resources, natural resources and environmental pollution Exploitation of non-renewable natural resources contributes to the deterioration of environmental resources. This is due to human behavior that does not protect the environment. The threat of climate change and global warming further reduces the sustainability of the earth. The research method used a type of qualitative research, descriptive in nature using analysis. Based on the subject's point of view is more emphasized in this qualitative research. data collection techniques and qualitative analysis are more emphasis on meaning. A literature study is a research conducted by researchers by collecting a number of books and magazines related to the problem and for research purposes. global warming such as carbon emissions, plastic waste, and other issues. causing damage to the environment. 1. maqashid al-syariah theory 2. preserving the environment 3. Environmental ethics theory a. Anthropocentrism theory,b. Biocentrism theory, c. Ecocentrism theory 4. The need for national banking on Green Banking In the field of financial institutions, especially banks, the green initiative adopted is Green Banking.1.Green reward 2. Green investment 3.Green building 4. Paperwork or paperless 5.Reuse/recycle/refurbish Green Banking is a concept that encourages sustainable and environmentally friendly practices in the banking industry. It involves initiatives such as green buildings, paperless operations, and recycling practices. The aim is to minimize the impact on the environment. Green Banking is part of the broader concept of a green economy, aiming to balance economic development with environmental sustainability. Bank Syariah Indonesia (BSI) is one of the banks in Indonesia that has implemented Green Banking practices